Auditing entrepreneurial service innovations. (1st September 2004) - Ozyilmaz, Adnan; Berg, Daniel
This study's objective was to develop an entrepreneurial service innovation audit model. Because the entrepreneurial service innovation literature was underreported, a case study research method explored the appropriateness and validity of the model. The three individual case studies demonstrate that the proposed model is valid. This study's results also explicitly identify the sub-dimensions that entrepreneurial service organisations need to use in auditing their service innovations. This is the first model, known to us, developed to audit entrepreneurial service innovations. The model can facilitate the growth of entrepreneurial services because it indicates the dimensions that can make an entrepreneurial service innovation successful.